Teacher perceptions of educational board games based on Pancasila values to increase student learning interest in Civics learning - Elisa Seftriyanai; Intan Indah Megasari (Inovasi Kurikulum, 2025)
This research aims to identify teachers' perceptions of using educational board games based on Pancasila values in increasing students' interest in learning Pancasila. This research uses a qualitative approach with a purposive sampling technique to select respondents from Pancasila Education teachers at the upper secondary and tertiary education levels. Data was collected through in-depth interviews and analysed using thematic analysis techniques, which allowed researchers to identify key patterns from the data collected. The research results show that most teachers have a positive perception of this educational board game. This media is effective in creating more interactive learning, increasing student involvement, and making it easier to understand abstract concepts such as Pancasila values. In conclusion, educational board games based on Pancasila values have great potential as an innovative learning tool that can increase students' interest in learning while integrating national values.   Abstrak Penelitian ini bertujuan untuk mengidentifikasi persepsi guru terhadap penggunaan board game edukatif berbasis nilai-nilai Pancasila dalam meningkatkan minat belajar peserta didik pada pembelajaran PPKn. Penelitian ini menggunakan pendekatan kualitatif dengan teknik purposive sampling untuk memilih responden yang terdiri dari guru-guru PPKn di tingkat pendidikan menengah atas dan perguruan tinggi. Pengumpulan data melalui wawancara mendalam dan dianalisis menggunakan teknik analisis tematik, yang memungkinkan peneliti mengidentifikasi pola-pola kunci dari data yang terkumpul. Hasil penelitian menunjukkan bahwa mayoritas guru memiliki persepsi positif terhadap board game edukatif ini. Media tersebut dianggap efektif dalam menciptakan pembelajaran yang lebih interaktif, meningkatkan keterlibatan peserta didik, dan mempermudah pemahaman konsep abstrak seperti nilai-nilai Pancasila. Kesimpulannya, board game edukatif berbasis nilai-nilai Pancasila memiliki potensi besar sebagai alat pembelajaran inovatif yang dapat meningkatkan minat belajar peserta didik sekaligus mengintegrasikan nilai-nilai kebangsaan. Kata Kunci: nilai Pancasila; permainan papan; PPKn